An Efficient and Low Noise L-band Erbium-Doped Fiber Amplifier - Harun, Sulaiman Wadi; Ahmad, Harith (Penerbit Universiti Sains Malaysia, 2004)
The use of the long-wavelength-band (Lband) is attractive for both increasing the capacity of wavelength division multiplexing (WDM) systems and has been used in WDM transmission experiments at over 1 Tb/s. Recently, a gain bandwidth of about 80nm has been achieved by integrating the L-band EDFA in parallel with conventional band (Cband) EDFA [1]. Moreover, the L-band EDFAs will make it possible to construct an effective WDM systems employing dispersion-shifted fiber (DSF) without the degradation caused by four-wave-mixing (FWM) [2]. The L-band erbium-doped fiber amplifier (EDFA) is studied because it can be constructed by silica-based erbium-doped fiber (EDF) and has a low linearity for WDM signals. However, L-band EDFAs have a low power conversion efficiency (PCE) compared to a C-band.